Non-Protein Coding RNA Genes As The Potential Markers For The Detection And Differentiation Of Salmonella Enterica Serovar Typhi And Salmonella Enterica Serovar Paratyphi A Using PCR - Ravichantar, Nithya (2014)
Non-protein-coding RNAs (npcRNAs) are not translated into protein but are key regulatory molecules in the cell. Recently, the expression of specific npcRNAs has been linked to various human diseases and cancer. Salmonellosis is a communicable disease caused by members of the Salmonella species, which infect humans through contaminated food or water. It is of paramount importance that accurate detection methods are available for differentiating the Salmonella serovars that produce severe infection in humans, including S. Typhi and S. Paratyphi A. The efficacy of using npcRNA genes from S. Typhi as molecular targets in detection and differentiation of S. Typhi and S.Paratyphi A using a a multiplex polymerase chain reaction (mPCR) assay was reported in this study. The detection limit for this mPCR assay was 10pg of gDNA. Moreover, in a stool-seeding experiment with S. Typhi and S. Paratyphi A, a respective detection limit of 1.5 x 101 and 1.5 x 100 CFU/mL following 4h of enrichment in selenite cystine broth offers an early clinical diagnostics. Collectively, this study has successfully developed npcRNA genes based mPCR that is able to detect and differentiate S. Typhi, S. Paratyphi A in a typhoid infection besides discriminating them from a general salmonellosis. With its comparable specificity and sensitivity level to other studies/ products, this mPCR could prove to be an excellent alternative for clinical diagnosis and disease monitoring of salmonellosis.